Multi-pinhole collimator design in different numbers of projections for brain SPECT - Huang, Wenbo; Mok, Greta S. P. (Frontiers in Medicine, 2023)
High resolution and sensitivity brain SPECT is promising for accurate diagnosis for Alzheimer's disease (AD) and Parkinson's disease (PD). Multi-pinhole (MPH) collimators with a good performance in imaging small field-of-view (FOV) could be better used for brain SPECT. In this study, we aim to evaluate the impact of varying the number of pinholes and the number of projections on the performance of MPH brain SPECT.The system design was based on a commercial clinical dual-head SPECT/CT scanner, with target spatial resolutions of 12 mm and 8 mm for AD and PD SPECT respectively. One to twenty-five pinholes were modeled for 64, 32, 16, 8, 4 and 2 projections. The 3D NURBSbased HUman Brain (NHUB) phantom was used in the analytical simulation to model 99m Tc-HMPAO and 99m Tc-TRODAT distributions. The 2D Derenzo hot-rod phantom and star phantom were used in Monte Carlo simulations to evaluate the spatial resolution and angular sampling performance of MPH. The influence of different detector positions was also evaluated for 2, 4 and 6 angular views. The projections were reconstructed using the 3D MPH ML-EM method. Normalized mean square error, coefficient of variation and image profiles were evaluated.Along with the decrease of the number of projections, more pinholes are required to achieve the optimum performance. For 32 projections, 9-and 7-pinhole collimator provide the best normalized mean square error (NMSE) to coefficient of variation (COV) trade-off for 99m Tc-HMPAO and 99m Tc-TRODAT respectively. Detector positions substantially affect the image quality for MPH SPECT for 2 and 4 angular views. The smallest rod size for Derenzo hot-rod phantom which could be resolved is 7.9 mm for MPH general purpose collimator (MPGP) with more than 16 projections and 6.4 mm for MPH high resolution collimator (MPHR) with more than 8 projections.The number of pinholes affect the performance of MPH collimator especially when the projection views become fewer. More pinholes are required for fewer projections to provide better angular sampling in MPH for complex activity distributions. Detector positions affect the image quality for MPH SPECT for 2 and 4 angular views, where L-mode acquisition is slightly superior to H-mode.